Propuesta para el aprovechamiento del lactosuero proveniente de la elaboración de queso ricotta por medio de separación por membranas (2021)
In this project, alternatives are proposed for the use of the whey from the production of Ricotta cheese by means of separation by membranes. The whey reaches approximately 8,750 L per month for the company, whose final disposal is directed towards the dumping, causing serious problems of corrosion and contamination of the water bodies; wasting the opportunity to generate added value to this by-product, which at the same time minimizes the impact on the environment. For the development of this project, the characterization of this whey was carried out, identifying the component of interest for its recovery, such as proteins, obtaining a value of 0.8 g / 100g in the whey. In this way, the membrane technologies that facilitate their separation are selected, determining the evaluation criteria contemplated in the hierarchical analysis method for microfiltration, ultrafiltration and nanofiltration technologies. As a result, microfiltration is chosen as the pretreatment stage and the ultrafiltration stage for protein recovery.